1989
DOI: 10.1111/j.1432-1033.1989.tb14485.x
|View full text |Cite
|
Sign up to set email alerts
|

The binding of double‐stranded RNA and adenovirus VAI RNA to the interferon‐induced protein kinase

Abstract: The protein kinase from human cells dependent on double-stranded (ds) RNA is a 68-kDa protein (p68 kinase), the level of which is enhanced significantly in cells treated with interferon. When activated by low concentrations of dsRNA, the p68 kinase becomes phosphorylated and thereby catalyzes the phosphorylation of the protein-synthesis initiation factor, eIF2. Here, we have purified the p68 kinase to homogeneity using a specific monoclonal antibody to investigate its capacity to bind dsRNA, poly(1). poly(C). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
79
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(86 citation statements)
references
References 41 publications
7
79
0
Order By: Relevance
“…This form can be dephosphorylated by a PP1-like phosphatase to regenerate the form of PKR with high affinity for RNA and low eIF2α kinase activity. This model for PKR activation is consistent with the finding that autophosphorylation of PKR, but not phosphorylation of eIF2α by autophosphorylated PKR, is inhibited by the adenovirus RNA inhibitor VA I RNA (41).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This form can be dephosphorylated by a PP1-like phosphatase to regenerate the form of PKR with high affinity for RNA and low eIF2α kinase activity. This model for PKR activation is consistent with the finding that autophosphorylation of PKR, but not phosphorylation of eIF2α by autophosphorylated PKR, is inhibited by the adenovirus RNA inhibitor VA I RNA (41).…”
Section: Discussionsupporting
confidence: 89%
“…The discovery of autophosphorylation sites in the dsRBD of PKR and the observation that one of those sites is near the protein/ RNA interface in a complex between the dsRBD and an RNA activator led us to speculate that phosphorylation could influence the RNA-binding properties of the enzyme (23,24,26). This is consistent with previous reports indicating that once autophosphorylated, PKR no longer responds to RNA regulators, including kinase inhibiting RNAs (41). Given the number of autophosphorylation sites found in PKR to date (10 sites mapped, possibly 14 total), we concluded that identification of sites involved in controlling RNA binding by site-directed mutagenesis may be problematical, particularly given the possibility that the phosphorylation effect on RNA affinity may be cumulative, with no particularly important single site (21)(22)(23)(24).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The antibody-bound DAI was washed four times with buffer I and three times with buffer II (10 mM Tris-HCl [pH 7.5], 100 mM KCl, 0.1 mM EDTA, 100 U of aprotinin per ml, 20% glycerol). DAI was eluted by using guanidinium hydrochloride and dialyzed as previously described (9). For production of polyclonal antibody, New Zealand White rabbits were subcutaneously injected with 100 g of the purified DAI expressed in E. coli along with an equal volume of Freund's complete adjuvant.…”
Section: Methodsmentioning
confidence: 99%
“…It is generally thought that dsRNA binding stimulates the autokinase activity of DAI and that autophosphorylation locks the kinase domain into a configuration that can bind and phosphorylate eIF-2␣ in the absence of dsRNA activators (8,9,20). The kinetics of activation are second order for enzyme concentration (20), and partially phosphorylated DAI purifies as a dimer, whereas unphosphorylated DAI exists as a monomer (21).…”
mentioning
confidence: 99%